2020
DOI: 10.1186/s12957-020-01925-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of non-schistosomal colorectal cancer and schistosomal colorectal cancer

Abstract: Aim: The purpose of this study was to compare clinicopathological features of patients with non-schistosomal and schistosomal colorectal cancer to explore the effect of schistosomiasis on colorectal cancer (CRC) patients' clinical outcomes. Methods: Three hundred fifty-one cases of CRC were retrospectively analyzed in this study. Survival curves were constructed by using the Kaplan-Meier (K-M) method. Univariate and multivariate Cox proportional hazard regression models were performed to identify associations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
3
18
1
Order By: Relevance
“…Ye et al [32] reported that intestinal schistosomiasis was a risk factor for CRC and that the lesions caused by the disease might be considered precancerous. Our previous study demonstrated that schistosomiasis was an independent worse prognosis for OS in CRC patients [13]. In this study, we further con rmed that schistosomiasis was an independent unbene cial prognosis factor for OS in CRC patients.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Ye et al [32] reported that intestinal schistosomiasis was a risk factor for CRC and that the lesions caused by the disease might be considered precancerous. Our previous study demonstrated that schistosomiasis was an independent worse prognosis for OS in CRC patients [13]. In this study, we further con rmed that schistosomiasis was an independent unbene cial prognosis factor for OS in CRC patients.…”
Section: Discussionsupporting
confidence: 75%
“…However, all these studies were based on the analysis of data of clinicopathological characteristics, in ammation based prognostic systems have been rarely reported in the literature. Besides, our previous study showed that schistosomiasis was an independent poor prognosis for CRC patients [13], and clinicopathological characteristics were differences between patients with schistosomal and nonschistosomal CRC [13]. But the evidence that chronic in ammatory process occurring in schistosomiasis playing an important role in CRC progression is not providing.…”
Section: Introductionmentioning
confidence: 94%
“…Schistosomiasis may affect the occurrence and development of CRC 48 , 49 . We report here that in patients with schistosomal CRC, schistosomiasis may promote the development of CRC by affecting the transformation of TAMs to the M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective analysis includes 338 patients with resected primary CRC at Qingpu Branch of Zhongshan Hospital affiliated to Fudan University, from January 2008 to August 2016. All of the operations followed the principle described previously [ 23 ]. The inpatient medical records and pathological reports were reviewed from the pathological system and Qingpu District Center for Disease Control and Prevention, and the patients were followed up by telephone.…”
Section: Methodsmentioning
confidence: 99%
“…OS is defined as the interval from the surgical operation date to the last follow-up or death caused by CRC. Inclusion criteria are as previously described [ 23 ]. Two expert pathologists reviewed HE-stained slides to determine the diagnosis and to restage the tumors according to the eighth edition of American Joint Committee on Cancer (AJCC).…”
Section: Methodsmentioning
confidence: 99%